Sosialisasi Pencegahan Stunting Dan Pemeriksaaan Kesehatan Pada Masyarakat Desa Tanjungmekar Kecamatan Pakisjaya - Gani, Ruslan Abdul; Setiawan, Edi; Achmad, Irfan Zinat; Mahardhika, Dhika Bayu; Aminudin, Rizki; Purbangkara, Tedi; Dimyati, Akhmad; Yudha Ryanto, Aria Kusuma (Universitas Pahlawan Tuanku Tambusai, 2025)
Public health problems such as stunting need serious attention, especially in young children. To prevent stunting, this service teaches participants the importance of routine health checks for pregnant women and young children, as well as balanced diet and nutrition. The aim of this community service project is to educate the local community about health checks and how to prevent stunting. Through training and counseling, participants gain useful information that they can use in their daily lives. The community targeted by this effort is in Tanjung Mekar Village, located in Pakisjaya District. By actively participating in this activity, it is hoped that the community will have a better understanding of stunting and the importance of preventing it. In addition, routine health check-ups are also a concern, as they provide details providing knowledge about the benefits of regular check-ups and early detection of possible problems. Public knowledge regarding the need for routine health checks and stunting prevention has increased thanks to this commitment, increasing from an average score of 56.33 in the first test to 84.17, an average increase of 27.83 or around 93% in the last test. To increase public awareness of the importance of routine health checks, this outreach program is very important.